The effects of service quality on customer satisfaction and loyalty of online food delivery services using a Modified SERVQUAL Scale a case study of Tacloban City - Tajo, Deniel Jeffrey I.; Turija, Maebyl U.; Yaokasin, Jym Joshner Y.
This study analyzed the influence of service quality on the customer satisfaction and loyalty of online food delivery platforms operating in Tacloban City. The OFD-SERV scale (Cheng et al., 2021) was used to examine the similarities and differences between the expectations and perceptions of customers concerning service quality that they experience from local OFD platforms. The study also evaluates the six service quality dimensions (reliability, maintenance of meal quality and hygiene or MMQH, assurance, security, system operation, and traceability) of the OFD-SERV scale by using a modern configurational approach such as the Fuzzy-set Qualitative Comparative Analysis (FsQCA) to assess the credibility of the proposed theories pertaining to relationships of the six dimensions on customer satisfaction and loyalty. After collecting data from 79 qualified respondents, the results show that customers are most satisfied with the security provided by OFD platforms and are least satisfied with the way OFD platforms maintain the meal quality and hygiene of their deliveries. The findings also reveal that Grabfood outperforms FoodPanda and Maxim in all six service quality dimensions of the OFD-SERV scale. In addition, the application of the FsQCA approach reveals equifinal configuration sets associated with the six dimensions and their casual relationships that lead to the outcomes of customer satisfaction and loyalty. The first configuration set for customer satisfaction contains the dimensions of reliability, assurance, system operation, and traceability. The second configuration set consists of reliability, MMQH, assurance, security, and system operation. Further, configuration sets for customer loyalty have the same service quality antecedents as the sets associated with customer satisfaction, with the addition of customer satisfaction also being an antecedent for customer loyalty. The sufficient condition analysis also shows that all OFD service quality dimensions and customer satisfaction are sufficient antecedents for their respective outcomes, indicating that the hypotheses proposed in this study were all accepted.